Factors Affecting Health-Related Quality of Life in Patients With Cholangiocarcinoma in the Northeastern Region of Thailand. Issue 6 (November 2015) - Woradet, Somkiattiyos; Promthet, Supannee; Songserm, Nopparat; Parkin, Donald M.
Abstract : Background: Cholangiocarcinoma (CCA) remains a major health problem and causes high mortality in Northeastern Thailand. Patients with CCA have a poor prognosis, and little is known about their health-related quality of life (HRQOL) and its determinants. Objective: The objective of this study was to investigate factors affecting HRQOL and its changes over time among CCA patients. Methods: Two hundred thirty-seven patients with CCA were recruited during a 6-month period in 2011 in 5 tertiary hospitals in 4 provinces of northeastern Thailand. Health-related quality of life after diagnosis of CCA was measured by the Functional Assessment of Cancer Therapy–Hepatobiliary questionnaire (Thai version 4). The HRQOL score of CCA patients at different times after diagnosis was compared by repeated-measures analysis of variance. Generalized estimating equation was used to identify factors affecting HRQOL among CCA patients. Results: Of 237 eligible patients registered, 99 confirmed cases completed follow-up at 2 months. Overall HRQOL varied over time, with the score at baseline being significantly lower than 1 and 2 months later. An adjusted analysis showed that patients who were 60 to 69 years old had higher HRQOL scores than did younger patients. Patients using alternative medicine had lower HRQOL scores than did those who did not. Conclusions: Health-related quality-of-life scores among CCA patients changed over time and were related to age at recruitment and use of alternative medicine. Implications for Practice: Healthcare providers should carefully communicate about the diagnosis and its implications. Patients with CCA, especially younger patients and those who have used traditional medicine, may benefit from counseling and help with mobilizing family and social support.